A constipação intestinal funcional em crianças e adolescentes na visão das mães: crenças, sentimentos, atitudes e repercussões sociais - Mariza Ferreira Leao (2007)
Functional constipation is a common pediatric problem. Although recent advances have contributed to improve the diagnostic and treatment of this disease, it is yet highly prevalent. Few efforts have been made in order to prevent it. Common sense and even physicians often believe that constipation is a benign disease in childhood and that children will grow out of it. Thus, a constipated child frequently remains untreated formany years and the disease affects their emotional and social functioning and also stresses his or her family. Nowadays, a biopsychosocial model is being proposed to understand this illness and its symptoms, showing that they are physiologically multidetermined and can be modified by sociocultural and psychological influences. A patients perceptions about his or her illness are also pointed out as relevant aspects to be accessed by physicians. Family-centered care is recommended as an important strategy to increase the effectiveness of the treatment. The decision to investigate a mothers perceptions of chronically constipated children was based on both, the medical, epidemiological, social and psychological relevance of this disease and on the fact that few studies about this aspect have been conducted in Brazil. This study contains two articles: the first shows the central role of the family on childs health and emphasizes the family-centered care as a new trend in the context of gastrointestinal disorders. The second is a qualitative study that explores mothers perceptions and management of functional constipation in her children. The author conducted in-depthinterviews with mothers of fourteen children receiving health interventions in a public tertiary gastropediatric center in Belo Horizonte, Brazil, for six months or longer. Four themes emerged from the analysis: definitions, causes and factors related to constipation; concerns, feelings and attitudes towards constipated child; family and social repercussion of the functional constipation and perceptions about cure, treatment and health care. Strong and negative feelings such as guilty and angry wererelated mainly among mothers of children with fecal soiling (mainly adolescents) and long history of these symptoms. The scene was quite different among those whose children had no fecal soiling or received early therapeutic intervention. The findings offer an insight into the mothers experiences with functional constipation in Brazil and indicate the need of health promoting education addressed to physicians and teachers in order to prevent chronicle constipation. A more sensitive approach for the mothers, including a therapeutic setting to facilitate the expression of their feelings towards their children is also recommended. We believe that these findings highlight the clinical significance of a mothers perceptions and attitudes in the treatment of chronicleconstipation and provide insights into one facet of the diseases biopsychosocial etiology.